Becoming multicultural : immigration and the politics of membership in Canada and Germany - Triadafilopoulos, Triadafilos (UBC Press, 2012)
In a world of nation-states, international migration raises questions of membership: Should foreigners be admitted to the national space? And should they and their children be granted citizenship? Canada and Germany's responses to these questions during the first half of the twentieth century consisted of discriminatory immigration and citizenship policies aimed at harnessing migration for economic ends while minimizing its costs. Yet, by the end of the century, the admission, settlement, and incorporation of previously excluded groups had transformed both countries into highly diverse multicultural societies. Becoming Multicultural explains how this remarkable shift came about. Triadafilopoulos argues that dramatic changes in global norms after the Second World War made the maintenance of established membership regimes difficult to defend, opening the way for the liberalization of immigration and citizenship policies. It is a thought-provoking analysis that sheds light on the dynamics of membership politics and policy making in contemporary liberal-democratic countries.